(untitled) (Patan Pragya, 2022)
This research aims to find out the effects of COVID-19 on the human resource development of Tribhuvan University, Nepal. The research follows a survey research design. It offers a brief analysis and an understanding of the human resource development at Tribhuvan University, Nepal during the COVID- 19 Pandemic. The total population of the study was 15196 employees (7966teaching faculties and 7230 non-teaching staff), 216 samples have been taken for this study. The convenient sampling technique has been applied for the selection of the respondents. The primary data were collected through a structured questionnaire. The data are analyzed and interpreted using descriptive and inferential statistics. The findings of the study reveal the human resource development and response to the COVID- 19 pandemic during the time of crisis Tribhuvan University, Nepal. The independent variables (Are work environment, motivation, health and safety, and organizational culture). The dependent variable is human resource development. It is revealed that the Tribhuvan University, Nepal has played a crucial role to develop human resources to face the challenges of the global pandemic through the utilization of motivation, making conducive working environment, and making the cultural environment friendly. The results show, that there is a positive and significant effect of motivation and health and safety on human resource development at Tribhuvan University. It can be concluded that all constituent colleges and higher educational institutions have also followed the same strategy across the country.